Complementary and Alternative Medicine Use by Patients with Inflammatory Bowel Disease: Are Canadian Physicians Failing with Conventional Therapy, or Not? - Charles N Bernstein (Canadian Journal of Gastroenterology)
Hilsden et al conducted a postal survey of members of the Crohn's and Colitis Foundation of Canada (CCFC), gathering data on the use of both conventional therapy and complementary and alternative medicine (CAM). The response rate was 76% (quite good for a mailed survey), although 9% of respondents stated that they did not actually have inflammatory bowel disease (IBD) (their data were excluded from the analysis). The data regarding CAM use were difficult to follow, as there was a blending of past and current reported use of CAM, as well as of CAM use specifically for IBD as opposed to for non-IBD reasons. Current or past use of CAM for IBD was reported by 47% of respondents, and ongoing use for IBD specifically was reported by 24%. It appears that most of the CAM used by IBD patients was not for their IBD. An important finding was that approximately half of IBD patients use CAM either for their IBD or for other reasons. The main CAM used was acidophilus (19%), followed by massage (18%) and flax seed (13%).